Novel agents for the treatment of lymphomas during pregnancy: A comprehensive literature review. (September 2021) - Luttwak, E.; Gurevich-Shapiro, A.; Azem, F.; Lishner, M.; Klieger, C.; Herishanu, Y.; Perry, C.; Avivi, I.
Abstract: Lymphoproliferative diseases occurring during pregnancy present unique diagnostic and therapeutic challenges aiming to achieve maternal cure without impairing fetal health, growth, and survival. These goals are further complicated by the fast-paced emergence of novel therapies and their introduction as standard of care, even in newly diagnosed patients. Due to the rarity of hematological malignancies in pregnancy and the exclusion of pregnancy in almost all clinical trials, available data on the fetal effects of novel drugs are limited to animal models and case reports. The current review addresses the entire multidisciplinary team involved in treating pregnant patients with lymphoproliferative diseases. We describe novel agents according to their mechanism of action, and summarize our knowledge of their effects during the gestational period, particularly those associated with fetotoxicity. Therapeutic dilemmas associated with the employment of these new agents are also discussed.